Numismatic Typeforms of the Numerals Zero through Ten in Medieval Europe: A Classification System - Spencer, David B. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
While the shapes of Latin letters (i.e. ‘letterforms’) and Western Arabic numerals (i.e. ‘typeforms’) have been studied on medieval European parchments and stone monuments, similar studies on typeforms from coin inscriptions are lacking. Therefore, the study goal was to analyze numeric typeforms in the available numismatic literature relating to 9th to 15th century Europe and create a classification system. The hypothesis was that the shape of the numerals would vary based on the timeframe and geographic location of the coins on which they were present. In total, 12 numismatic books representing 22 geographic regions were analyzed and the numerals’ typeforms from more than 900 coins categorized. The numeral typeform frequency for the classification system was then compared with the typeform frequency for the author’s collection. The vast majority (>95%) of numerals found in the literature specified the date of the coins, with heavy representation from 15th century Netherlands, Germany, and Austria. There was good agreement in the relative frequencies of the numerals between the literature and the author’s collection, with the numerals one and four being most prevalent in both sources.